Growth performance and virulence of Pyricularia oryzae toward Malaysian rice varieties / Zuliana Azwin Mohd Jamaluddin - Mohd Jamaluddin, Zuliana Azwin (Faculty of Plantation and Agrotechnology, 2018)
Rice is the most important crop in the world. In Malaysia, the government had to import rice due to insufficient supply of rice for our local consumer. Besides, many chemicals are being used to increase the production of rice and to overcome pests and diseases problem and this result in the emergence of resistant pests and diseases. One of the most devastating diseases of rice is blast caused by Pyricularia oryzae (P. oryzae). The disease was widely spread in this country where the first incidence was in Penang. Unfortunately, there is still no research regarding the effect of blast disease on rice varieties in Melaka. Therefore, a study about this fungus should be conducted to know the virulence of P. oryzae on local rice variety. The sample collection for fungal isolation was taken from three different regions which are in Alai, Bukit Lintang and Merlimau, Melaka. Severely affected tillers showing blast symptoms was randomly sampled with the help of an experienced farmer. After the fungal isolation, single tips of mycelia was used to identify the morphological characteristics of P. oryzae. The most vigorous growth of the P. oryzae from three different locations was undergone pathogenicity test using MR 220CL2, MR 269 and MARDI Siraj 297 in the greenhouse. The severity of each treatment was recorded for one week. Based on three location studied, it can be concluded that the highest from Merlimau. The result of the pathogenicity test was the MARDI Siraj 297 is the moderate resistance and the lowest was MR 220CL2 which quite susceptible to blast disease.